Penyuluhan dan Demonstrasi Tentang Perawatan Payudara pada Ibu Hamil Sebagai Upaya Persiapan Pemberian ASI Ekslusif - Tati Karyawati; Siti Fatimah; Ahmad Zakiudin (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
This study explains the importance of exclusive breastfeeding (EBF) for babies because it provides the necessary nutrients and antibodies to protect them from various diseases. Low EBF can increase infant mortality. Although there has been an increase in EBF globally, it is still below the 50% target set by the World Health Organization (WHO) for the period 2015-2020. In Indonesia, the percentage of EBF for infants aged 0-5 months has increased to 71.58% in 2021 from 69.62% in the previous year, but some provinces still have percentages below the national average. Lack of education, socialization, advocacy, and campaigning towards successful breastfeeding is a problem in achieving EBF. The method used in this study is counseling and demonstration methods about improper breast care can lead to insufficient milk supply, and mothers need support and information to prepare for breastfeeding. Proper breast care can help mothers produce enough milk, prevent breast infections, and detect breast abnormalities. Health education about breast care is most effective when given to pregnant women during the third trimester. The study concluded that providing health education about proper breast care during pregnancy is critical to encouraging EBF and improving infant health.